Comparison of proteins with anti-influenza virus effects in parotid and submandibular-sublingual saliva in humans - Kenkichi Yamamoto; Shinji Yamamoto (BMC, 2022)
Abstract Background Saliva possesses antiviral activity, with submandibular-sublingual (SMSL) saliva having higher antiviral activity than parotid saliva. Various salivary proteins have inactivating effects on influenza A virus (IAV), but the detailed relationship between antiviral proteins and salivary anti-IAV activities in the parotid and SMSL glands is unknown. Here, to identify salivary proteins with anti-IAV activity, salivary proteins from parotid and SMSL glands were identified, quantified, and compared using liquid chromatography-mass spectrometry. Methods Twelve healthy male volunteers participated in the study. Parotid and SMSL saliva was collected by suction and collection devices. We assessed anti-IAV activities, protein concentrations, and protein-bound sialic acid concentrations in parotid and SMSL saliva. Results SMSL had significantly higher anti-IAV activity than parotid saliva. SMSL also had higher concentrations of glycoproteins, such as mucin 5B and mucin 7, protein-bound sialic acid, cystatins, and lysozyme C, compared with parotid saliva. Salivary mucin 5B and mucin 7 concentrations significantly positively correlated with the salivary protein-bound sialic acid concentration. Salivary anti-IAV activity significantly positively correlated with protein-bound sialic acid, mucin 5B, mucin 7, cystatin-C, -S, and -SN concentrations. Conclusion Salivary mucins, cystatins, and lysozyme C contribute to the high anti-IAV activity of SMSL saliva.